A New Genus of Microdontine Flies (Diptera: Syrphidae) With Notes on the Placement of the Subfamily - F. Christian Thompson (Psyche: A Journal of Entomology)
I discovered the following new genus o Syrphidae while reviewing the Neotropical Microdontinae. I had planned to put aside its description until my study of the subfamily was finished. However, publication of a second species assignable to it by van Doesburg (1966) has necessitated publishing a name now for this genus so that it can be incIuded in the Catalog of South American Diptera.